Conventional Ultra-high Molecular Weight Polyethylene versus Highly Cross-linked Polyethylene from Semi-constrained, Fixed-bearing Total Ankle Arthroplasty Systems: A Comparison of Wear Characteristics. Issue 3 (14th September 2018) - Schipper, Oliver; Haddad, Steven; Fullam, Spencer; Pourzal, Robin; Wimmer, Markus
Category: Ankle Arthritis Introduction/Purpose: The aim of this study was to compare the polyethylene wear rate, particle size, and particle shape of primary semi-constrained, fixed-bearing, bone-sparing total ankle arthroplasty using conventional ultra-high molecular weight polyethylene (CPE) versus highly cross-linked polyethylene (HXLPE) by applying a level walking input using a joint simulator. Methods: Two fixed-bearing total ankle replacement systems with different types of polyethylene liners were tested: 1.) CPE sterilized in ethylene oxide, and 2.) HXLPE sterilized with gas plasma after electron beam irradiation. Three implants for each design underwent wear testing using gravimetric analysis over 5 million simulated walking cycles. A fourth implant was used as a load soak control. Equivalent circle diameter (ECD) and equivalent shape ratio (ESR) were computed to determine particle size and particle shape, respectively. Results: The mean wear rate from 1.5-5 million cycles (MC) was 2.0±0.3mg/MC for HXLPE and 16.7±1.3mg/MC for CPE (P < 0.001). The total number of particles per cycle generated for HXLPE and CPE were 0.17x106 particles/cycle and 0.53x106 particles/cycle, respectively (P < 0.001). The mean ECD of HXLPE particles (0.22 ±0.11μm) was significantly smaller than the mean ECD of CPE particles (0.32±0.14μm) (P<0.001). HXLPE particles were significantly more round than CPE particles (P<0.001). Conclusion: HXLPE liners had a significantly lower wear rate and produced significantly fewer and rounder particles than CPE liners. The results of this study suggest that HXLPE has more favorable wear characteristics for total ankle arthroplasty.